2022
DOI: 10.22146/ijc.70146
|View full text |Cite
|
Sign up to set email alerts
|

Codoping Effect of Nitrogen (N) to Iron (Fe) Doped Zirconium Titanate (ZrTiO<sub>4</sub>) Composite toward Its Visible Light Responsiveness as Photocatalysts

Abstract: Iron (Fe) and nitrogen (N) were introduced as dopants into zirconium titanate (ZrTiO4) in order to study the codoping effects of nitrogen on iron-doped zirconium titanate (Fe,N-codoped ZrTiO4) composite. Titanium tetraisopropoxide (TTIP), zirconia (ZrO2), urea, and iron(II) sulfate heptahydrate were used as the source of TiO2, semiconductor supports, source of nitrogen, and iron, respectively. A specific amount of iron (1, 3, 5, 7, and 9 wt.%) and a fixed nitrogen content (10 wt.%) were doped into the ZrTiO4 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The E g is reduced up to 5% Cu doping, then is increased again as copper concentration increases as well. Cu doping with excess concentration can cause sintering, which forms aggregates that are not evenly distributed [24]. The E g of ZrTiO 4 is slightly smaller due to the broad E g of ZrO 2 mixing with the relatively narrow E g of TiO 2 until the equilibrium is reached.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The E g is reduced up to 5% Cu doping, then is increased again as copper concentration increases as well. Cu doping with excess concentration can cause sintering, which forms aggregates that are not evenly distributed [24]. The E g of ZrTiO 4 is slightly smaller due to the broad E g of ZrO 2 mixing with the relatively narrow E g of TiO 2 until the equilibrium is reached.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This coupling will offer the added benefits of large surface area, high thermal stability, and corrosion resistance [20]. Doping of ZrTiO 4 with metals, such as Fe [21], Mn [22], and Zn [23], as well as non-metals such as N [24] and C [25], has been reported to decrease the band gap to visible light. Copper (Cu) and nitrogen (N) have been chosen as the dopants for this work, as they both have excellent efficiency in separating the charge carriers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Zirconium titanate (ZrTiO 4 ) modified by the doping method will decrease the band gap to visible light. Several studies have reported that doping can be done with metals such as Fe [26], Mn [27], and Zn [28] and also non-metals such as N [29] and C [30]. In this study, copper (Cu) and nitrogen (N) were chosen as dopants because they have good charge-carrier separation efficiency.…”
Section: Figmentioning
confidence: 99%